Nanoporous Cu(I) Metal–Organic Framework: Selective Adsorption of Benzene and Luminescence Sensing of Nitroaromatics. Issue 10 (11th April 2017) - Santra, Atanu; Francis, Maria; Parshamoni, Srinivasulu; Konar, Sanjit
Abstract: A porous two–dimensional Cu(I) Metal–Organic Framework (MOF) with 4 4 net {[Cu(L)(I)]⋅(DMF)⋅H2 O} n (1 ); L=4′‐(anthracen‐9‐yl)‐4, 2′:6′, 4′′‐terpyridine; DMF=N, N‐dimethylformamide) was synthesized employing solvothermal technique. Single crystal X‐ray analysis reveals that the 2D 4 4 nets in1 are interdigitated with each other to generate a supramolecular 3D framework, contains 1D pore with π‐ electron‐rich pore surfaces decorated with pendant anthracene moiety of linker L. The adsorption properties of activated framework1 were investigated and it exhibited preferential affinity for benzene and can successfully separate benzene from its nonaromatic analogue like cyclohexane under ambient conditions. Furthermore, the luminescent study indicated that compound1 can sensitively and selectively detect highly explosive nitroaromatic compound (TNP; 2, 4, 6‐trinitrophenol), even in presence of other nitroanalytes via fluorescence quenching mechanism. More importantly, recyclability and sensitivity studies have revealed its reusability for several times and detection limit towards TNP is at the parts per billion (ppb) levels. This is a promising material of dual functionalities such as separation of benzene from cyclohexane and selective nitroarometic sensing. Abstract : A novel Cu(I) framework with with pores decorated with pendant anthracene moiety exhibits selective adsorption of benzene over cyclohexane. Moreover, it can sensitively and selectively detect highly explosive nitroaromatic compound (TNP; 2, 4, 6‐trinitro‐ phenol) with detection limit at the parts per billion (ppb) levels.